2009
DOI: 10.2174/1874088x01004010005
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Self-Cleaning Properties of Ag-Doped TiO2

Abstract: Commercially available TiO 2 of anatase structure produced in the Chemical Factory Police S.A. was modified by doping Ag from AgNO 3 solution via photodeposition method. The obtained amount of deposited Ag on TiO 2 was in the range of 0.11 to 0.98 mass %. Deposition of Ag on TiO 2 resulted in the retarding of the recombination reaction and formation of the higher amount of OH radicals on the photocatalyst surface during irradiation with UV light. The photocatalytic activity of samples was tested for the decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
(18 reference statements)
1
28
0
Order By: Relevance
“…61 Increased adsorption capacity of TiO 2 with Ag-doping has been reported, 62,63 but this effect has not been consistently observed. 64,65 For the photocatalysts synthesized in this present study, a reduction in degradation rate was observed. According to Ramos et al,14 this possibly occurs because maximum saturation is reached on the semiconductor surface and excess silver occupies active sites in the catalyst, decreasing catalytic activity by lowering the incidence of radiation on TiO 2 particles and decreasing the number of active sites for substrate adsorption.…”
Section: Investigation Of Photocatalytic Efficiencymentioning
confidence: 63%
“…61 Increased adsorption capacity of TiO 2 with Ag-doping has been reported, 62,63 but this effect has not been consistently observed. 64,65 For the photocatalysts synthesized in this present study, a reduction in degradation rate was observed. According to Ramos et al,14 this possibly occurs because maximum saturation is reached on the semiconductor surface and excess silver occupies active sites in the catalyst, decreasing catalytic activity by lowering the incidence of radiation on TiO 2 particles and decreasing the number of active sites for substrate adsorption.…”
Section: Investigation Of Photocatalytic Efficiencymentioning
confidence: 63%
“…Photoactivity of TiO 2 , according to its application, can be reduced or increased through coupling [4], dye sensitization [2,5], and surface modification [6][7][8][9][10][11][12] and also doping metals, nonmetals or ionic compounds into the crystal structure [13,14] of the TiO 2 . In coatings industry, improve the properties and/or develop functional coatings via incorporation the nanoparticles such as TiO 2 nanoparticles have received many attractions, both in industry and in academia.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of solid present in the paint was determined by drying 1 g of paint in a clean, dry watch glass. Based on the initial and final weight measurements, the solid content of TiO 2 .Fe 2 O 3 paint was evaluated using the following equation (1). …”
Section: Solid Content Measurementmentioning
confidence: 99%
“…Ag doped TiO 2 shown the best retention of photo activity. Irradiation of the coatings resulted in an increase in wettability [1]. Monoclinic structure of metal oxide nanoparticle was synthesized by aqueous precipitation method [2].…”
Section: Introductionmentioning
confidence: 99%